Islamic Religious Education Learning Strategy for Mentally Disabled Children - Rosadi, Imron; Anwar, Mohamad Fauzan; Rahmatullah, Mohamad (Institute Of Advanced Knowledge and Science, 2024)
Children with intellectual disabilities often face challenges in the learning process because their academic abilities are less than expected, so they require special learning approaches and methods. This research aims to explain the planning, implementation and supporting and inhibiting factors for learning Islamic Religious Education at the Tunas Mulia Tanjung Ampalu Special School (SLB). The method used is a qualitative method. Data was taken and collected through interviews (school principals, teachers and students), observation and documentation. Research shows that teachers prepare to learn before starting the teaching process. These activities are outlined in teaching materials. The learning process has three activities, namely, the first activity is a preliminary activity carried out by the teacher before entering the class and the learning material. The second core, these activities are the activities carried out in the learning process, including methods, media and so on. Third, closing, namely activities carried out by teachers to strengthen students' understanding. Meanwhile, the supporting factors in learning are that students want to come to school to learn, the school facilitates learning media, teachers use interesting learning media and there are no fees charged. The inhibiting factors are that students are not yet fluent in reading the Al-Qur'an, students' attendance is irregular and there is a lack of infrastructure at the school.